Cuidar do ofício, para melhor cuidar: uma investigação em clínica da atividade junto aos cuidadores de pessoas com deficiência mental em uma organização privada, em Minas Gerais - Giselle Reis Brandao (2012)
The present investigative study is consisted of an intervention in Clinic of Activity, which is one of the Workplace Clinics, in the field of Work Psychology. It was conducted according to two main objectives. The first one was to investigate the methodological choices and their effect on the development of the carers of people with mental disabilities' activity in a private organization in Minas Gerais. We had a special interest in the methodological resources used in clinic of activity as promoters of potential psychological development for such professionals. To us, that experience was connected with another intervention experience which was previously carried out at the same organization, upon the foundations of psychosocial and organizational psychologies, with references to the methods of research-action, of Psychosociology, from where we derived some questions concerning what a psychologist is indeed capable of accomplishing in an intervention. Under this light, we brought forth the second objective of this study, which was using this experience in clinic of activity as a means of rethinking our professional journey, by placing new possibilities in the practice of work psychology in its core. For that purpose, we employed the historic-developmental methodology of clinic of activity, which is founded upon Vygotski and Clot, and the method of instruction to the double by working closely with six careres who alternate in taking care of the special male group. As propounded in the methodology, we conducted our study at first by executing the intervention, and then the research which gave birth to this dissertation. The results were organized into three objects of analysis, which define this research. The first object dealt with the possibilities of adopting the methodology and the method of instruction to the double, assessing their possibilities and the difficulties that were found. We stress the choices like the construction of the demand on the part of the carers, the establishment or lack thereof of the propounded methodology, and the questions referring to the use of the method of instruction to the double. In that respect, we were able to identify that the method enabled them to live a different experience and there to develop their activity, hence confirming their potential for interventions in workplace situations. The second object was the dialectics between the activity and the craft of caring, which are revealed through the dialogical interaction between professionals, and which has since capacitated us for better apprehending the particularities of their work. Our investigation has lead us to confirm the degenerateness of the professional genre, which is one of the four instances of the craft and which constitutes our third object. This means that the professionals who were investigated are deprived of reference to a work collective, the psychological and social function of which is to help them respond to conflicts and to recreate those norms which lack effectiveness. Even so, the conversations showed that there was a work of co-analysis, and, in that effort, the demand could be wrought, functioning thus as a source of action for them, both individually and collectively. This whole incipient experience has enabled us to recover and answer to old questions, and also to develop our methodological practice and, through it, our craft as work psychologists.